Circulating Non-coding RNAs in Renal Cell Carcinoma—Pathogenesis and Potential Implications as Clinical Biomarkers - Barth, Dominik A.; Drula, Rares; Ott, Leonie; Fabris, Linda; Slaby, Ondrej; Calin, George A.; Pichler, Martin (Frontiers in Cell and Developmental Biology, 2020)
Liquid biopsy – the determination of circulating cells, proteins, DNA or RNA from biofluids through a “less invasive” approach – has emerged as a novel approach in all cancer entities. Circulating non-(protein) coding RNAs including microRNAs (miRNAs), long non-coding RNAs (lncRNAs) and YRNAs, can be passively released by tissue or cell damage or actively secreted as cell-free circulating RNAs, bound to lipoproteins or carried by exosomes. In renal cell carcinoma (RCC), a growing body of evidence suggests circulating non-coding RNAs (ncRNAs) such as miRNAs, lncRNAs and YRNAs, as promising and easily accessible blood-based biomarkers for the early diagnosis of RCC as well as for the prediction of prognosis and treatment response. In addition, circulating ncRNAs could also play a role in RCC pathogenesis and progression. This review gives an overview over the current study landscape of circulating ncRNAs and their involvement in RCC pathogenesis as well as their potential utility as future biomarkers in RCC diagnosis and treatment.